Mindanao ; Couple power ; Bagong tunog [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Focuses on Mindanao plebiscite held to determine whether the provinces want to be autonomous ; marriage encounter in their 20th anniversary and the Bagong Lumad with its new sound especially in the advertising world.